2017
DOI: 10.1016/j.ijrobp.2017.06.976
|View full text |Cite
|
Sign up to set email alerts
|

The Updated Results for the Phase 3 Study of 5×5 Gy Followed By Chemotherapy in Locally Advanced Rectal Cancer (STELLAR trial)

Abstract: This study aimed to investigate the pntential of metformin to inhibits the growth and metastasis with enhancement of radiation response in hepatocellular carcinoma (HCC) xenograft mice model. Materials/Methods: Huh-7 HCC cells were injected to the right thigh in Balb/c nude mice. Huh-7 bearing mice were treated with local tumor irradiation with a single 15 Gy of X-ray (RT), intraperitoneal administration of metformin with 150 mg/kg/day until the day of sacrifice (MET), or combination of both (administration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…After a median follow-up of 59 months, patients who received consolidation chemotherapy were found to have improved DFS ( P < 0.05), and there were differences in survival between groups in patients who received at least one cycle of FOLFOX. In another phase III study [ 21 ] (STELLAR trial) in China, comparing short-course radiotherapy followed by chemotherapy with long-course chemoradiotherapy in LARC, the results showed that pCR rates in the experimental and control group were 18.6% vs. 5.4% ( P = 0.029), respectively. These findings were consistent with the pCR rates reported in this study (18.1–25%).…”
Section: Discussionmentioning
confidence: 99%
“…After a median follow-up of 59 months, patients who received consolidation chemotherapy were found to have improved DFS ( P < 0.05), and there were differences in survival between groups in patients who received at least one cycle of FOLFOX. In another phase III study [ 21 ] (STELLAR trial) in China, comparing short-course radiotherapy followed by chemotherapy with long-course chemoradiotherapy in LARC, the results showed that pCR rates in the experimental and control group were 18.6% vs. 5.4% ( P = 0.029), respectively. These findings were consistent with the pCR rates reported in this study (18.1–25%).…”
Section: Discussionmentioning
confidence: 99%
“…The locoregional failure rates (8.7% vs 6.0%; P = .10) and quality of life were similar between the two arms. The full manuscript of the RAPIDO trial and results of the STELLAR trial are awaited 29 . During the COVID pandemic, while the patient awaits surgery after SCRT, consolidation chemotherapy may be added and, to reduce toxicity, dose reductions may be considered.…”
Section: Discussionmentioning
confidence: 99%
“…10 A longer interval from radiation to surgery results in greater tumor downstaging for both SCRT 10 and LCCRT. 14 Furthermore, the incorporation of SCRT into TNT has been evaluated with promising results, [15][16][17][18][19] and although still under active investigation, 20,21 our colorectal disease management team concluded that delivering TNT with SCRT off-trial is reasonable and necessary given the ongoing COVID-19 pandemic. Admittedly, other potential differences between SCRT and LCCRT have not yet been fully understood (eg, in the context of nonoperative management and long-term anal sphincter function).…”
mentioning
confidence: 99%